2012
DOI: 10.1117/12.923716
|View full text |Cite
|
Sign up to set email alerts
|

Selection of bi-level image compression method for reduction of communication energy in wireless visual sensor networks

Abstract: Wireless Visual Sensor Network (WVSN) is an emerging field which combines image sensor, on board computation unit, communication component and energy source. Compared to the traditional wireless sensor network, which operates on one dimensional data, such as temperature, pressure values etc., WVSN operates on two dimensional data (images) which requires higher processing power and communication bandwidth. Normally, WVSNs are deployed in areas where installation of wired solutions is not feasible. The energy bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The design goal for JBIG2 was to provide lossy compression with almost no visible degradation of quality and to provide a higher compression ratio as compared to other lossless compression schemes [36]. It offers better compression ratios as compared to the existing lossless compression schemes [4][29] [36]. A typical JBIG2 encoder decomposes the input bilevel image into several regions and codes these regions separately using a different coding method.…”
Section: Jbig2 Compression Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design goal for JBIG2 was to provide lossy compression with almost no visible degradation of quality and to provide a higher compression ratio as compared to other lossless compression schemes [36]. It offers better compression ratios as compared to the existing lossless compression schemes [4][29] [36]. A typical JBIG2 encoder decomposes the input bilevel image into several regions and codes these regions separately using a different coding method.…”
Section: Jbig2 Compression Methodsmentioning
confidence: 99%
“…Khursheed et al [4] have investigated the bi-level compression schemes on a personal computer (PC). However, the FPGA based embedded platform has different constraints and requirements as compared to a PC.…”
Section: Compression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The architecture from 3 is shown in Figure 2. Based on this general architecture, we investigated the compression efficiency of the various bi-level image compression standards and presented the results in 4 . We concluded in 4 that, JBIG2 5 , CCITT Group4 6 and Gzip_pack 7 provide better compression efficiency (JBIG2 is developed by Joint Bi-level Image Experts Group i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The architecture from [6] is shown in Figure 2. Based on this general architecture, we investigated the compression performance of various bi-level image compression standards in [7,18] and concluded that JBIG2 [8], CCITT Group 4 [9] and Gzip_pack [10] provide good compression efficiency…”
Section: Introductionmentioning
confidence: 99%